Patients’ expectations and experiences with the usage of a self-care application for heart failure: A qualitative interview study - Anne Neumann; Bianca Steiner; Marlo Verket; Niveditha Daneeza Dinesh Kanna; Loreena Hill; Anne McNulty; Josiane J. J. Boyne; Marguerite Murphy; Yannick Maaser; Donna Fitzsimons; Matthew Barrett; Chantal F. Ski; et al. (Digital Health, 2024)
Background Heart failure (HF) is a chronic disease characterized by high mortality and healthcare expenditures. Digital health solutions, including mobile health applications (apps), offer opportunities to enhance patients’ self-care and quality of life. This qualitative study aimed to explore expectations, experiences, and usage behaviour of HF-patients regarding a self-care app ( DoctorME app). Methods Semi-structured interviews were conducted at 2-3 weeks (initial: n = 38), and 4–6 months (post: n = 45) of app use across four European countries. Most patients were male (initial: 84%; post: 78%), aged 60–69 years (initial and post: 29%), with mild HF symptoms. Interviews were transcribed, pseudonymised, and analysed using qualitative content analysis. Results Five key themes were identified: 1) expectations , 2) perceived usability and benefit, 3) usage behaviour and experiences, 4) self-care, and 5) social influences. Patients expected and valued continuous monitoring of vital signs and weight, early detection of deterioration, and quick feedback. The app was considered user-friendly, with most patients using it as recommended (eight times per month). Those reporting improved self-care attributed it to increased awareness and a sense of security. Patients with established self-care routines did not perceive any additional benefit. Patients’ perceptions on the impact of healthcare professionals’ and relatives opinions on app use were divided. Conclusions User-friendliness, continuous monitoring, rapid feedback, and e-learning modules are crucial for integrating self-care apps into daily HF care. While technical reliability and individualisation may enhance long-term use, most HF patients considered the app as a complement to, not a replacement for, professional healthcare guidance.